Desain dan Simulasi Screw Press Mesin Pencetak Briket - Imam Arif Ramadhan; Ali Hasimi Pane; Intan Zahar (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
Screw Press es are used to push and coMPact briquette raw materials into molds. One problem with Screw Press es is damage caused by friction and pressure acting on the machine, which necessitates simulation using Computer-Aided Engineering (CAE). This study aims to simulate the Screw Press  design and the distribution of stress and strain (von Mises). The material used is aluminum 6082-T6 with a yield strength of 280 MPa and an ultimate strength of 310 MPa. The results show that the Screw Press  design simulation with load variations of 2 N, 4 N, and 6 N has maximum stresses of 4.9 MPa, 5.08 MPa, and 5.26 MPa, respectively, and maximum strains of 6.99, 7.22, and 7.47, respectively, and a safety factor at the maximum scale value (≈15). This study contributes to the identification of potential local plasticity at the base of the Screw Press  of the briquette molding machine as a design consideration. Overall, the Screw Press  structure is still below the material yield limit and is declared safe.